2010
DOI: 10.2214/ajr.09.3036
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Hepatic Iron Deposition in Patients With Liver Disease: Comparison of Chemical Shift Imaging With Single-Echo T2*-Weighted Imaging

Abstract: Routine chemical shift imaging and single-echo T2*-weighted imaging have excellent diagnostic performance for detection of significant hepatic siderosis (grade >or= 2). Concomitant steatosis lowers the diagnostic performance of both sequences without reaching significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 38 publications
2
16
0
Order By: Relevance
“…Interestingly, the detection level of the both methods, visual grading and rSI difference, are consistent with the recently published observation by Alú stiza and Castiella [14]. In a recent retrospective study by Lim et al [18], routine in-phase and out-of-phase imaging was found to be of value for detection of significant hepatic siderosis in patients with chronic liver disease. Although they compared iron indexes with a semi-quantitative reference standard, the results are in good agreement with our study.…”
Section: Discussionsupporting
confidence: 88%
“…Interestingly, the detection level of the both methods, visual grading and rSI difference, are consistent with the recently published observation by Alú stiza and Castiella [14]. In a recent retrospective study by Lim et al [18], routine in-phase and out-of-phase imaging was found to be of value for detection of significant hepatic siderosis in patients with chronic liver disease. Although they compared iron indexes with a semi-quantitative reference standard, the results are in good agreement with our study.…”
Section: Discussionsupporting
confidence: 88%
“…This was not feasible using previously proposed methods, as discussed e. g. in [4,21]. By utilizing the fact that SIR-ULM correlates linearly to LIC for the smallest T E used, we were able to derive a relationship for the whole LIC range covered by our patient cohort, with the only exception being small, i. e. normal, LIC values.…”
mentioning
confidence: 92%
“…Therefore, there have been attempts at noninvasive in vivo methods for hepatic iron quantifi cation, such as superconducting quantum interference devices, magnetic resonance (MR) imaging, and dual-energy (DE) computed tomography (CT) (5)(6)(7)(8)(9)(10). In the past, DE CT had to be separately performed with sequential scanning at different energies, inevitably leading to redundant postprocessing time and spatial and temporal misregistration artifacts.…”
Section: Phantom Studymentioning
confidence: 99%